FENOTIPIK AGRONOMIS JAGUNG MANIS (Zea mays saccharata, Sturt) DI KECAMATAN MARPOYAN DAMAI PEKANBARU - Surtinah Surtinah (Jurnal AGROSAINS dan TEKNOLOGI, 2018)
The aim of the study was to obtain varieties that provide the best agronomic results in the Marpoyan Damai location. The treatment design used is Varieties consisting of three varieties, namely; v1 = Sweet Boy, v2 = Sweet Lady, v3 = Bonanza, the environmental design used was a completely randomized design, with six replications. Data were analyzed by variance, and followed by Duncan's 5% distance test. Observations were made on the weighted cob, weight of cob without weight, cob length, ear length without weights, ear diameter, and sugar content of sweet corn seeds. The results obtained were Sweet Boy variety varieties which are the best varieties recommended to be developed at the Marpoyan Damai planting site.